A chronostratigraphic framework for the Upper Jurassic Morrison Formation, western USA - Maidment,S; Muxworthy,A (Journal of Sedimentary Research, 2019)
The fluvial, overbank, and lacustrine deposits of the Upper Jurassic Morrison Formation of the Western Interior, U.S.A. have been intensively studied due to their diverse and well-preserved dinosaurian fauna, and the presence of economic quantities of uranium and vanadium ores. The formation crops out over 12 degrees of latitude and 1.2 million km2, and is an excellent case study for the examination of paleoecology, community structure, and evolutionary dynamics at a time in Earth’s history when the climate was significantly warmer than today. However, paleoecological studies have been hampered by lack of correlation across the formation. Assuming a primarily tectonic control on fluvial architecture, we propose the first chronostratigraphic framework of the formation, which is based on sequence stratigraphy, magnetostratigraphy, and radiometric dating. The formation can be divided into three sequences each represented by a period of degradation followed by aggradation. This chronostratigraphic framework indicates that the formation youngs to the north, and was deposited over about 7 million years during the late Kimmeridgian and Tithonian. This framework provides a foundation for future sedimentological, stratigraphic, and paleobiological studies of the iconic dinosaurian fauna known from the Morrison.